2022
DOI: 10.1177/11206721221091375
|View full text |Cite
|
Sign up to set email alerts
|

Dry eye in Sjögren's syndrome – characteristics and therapy

Abstract: Background Sjögren's syndrome is an autoimmune disease, and its important feature is the lymphocyte infiltration of exocrine glands, including lacrimal glands. It contributes to defects of their activity and causes that one of the main manifestation of Sjögren's syndrome is dry eye. Unfortunately, the discrimination between dry eye related and non-related to Sjögren's syndrome is difficult at the initial stages of diseases. In addition, the available agents for the treatment of Sjögren's syndrome-related dry e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 106 publications
(117 reference statements)
0
18
0
Order By: Relevance
“…Therefore, vitamin D may be an agent supporting the available treatment of eye disorders. For example, it has been suggested that deficiency of the vitamin D occurs in patients with Sjögren’s Syndrome-related dry eye, and this may result in a modulation of the clinical course [ 201 ]. That is why vitamin D may be considered as a modulator of the clinical course of ocular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, vitamin D may be an agent supporting the available treatment of eye disorders. For example, it has been suggested that deficiency of the vitamin D occurs in patients with Sjögren’s Syndrome-related dry eye, and this may result in a modulation of the clinical course [ 201 ]. That is why vitamin D may be considered as a modulator of the clinical course of ocular diseases.…”
Section: Discussionmentioning
confidence: 99%
“… Patients with SSDE may be asymptomatic or mildly symptomatic despite signs of significant ocular inflammation [ 74 ]. Reliable and effective screening tools and algorithms to determine which DED patients should be worked up for SS are lacking [ 4 ]. Ophthalmologists underestimate the importance of SS and consequently refer few patients with DED for SS workup [ 75 ].…”
Section: Current Diagnostic Challenges Encountered By Cliniciansmentioning
confidence: 99%
“…Reliable and effective screening tools and algorithms to determine which DED patients should be worked up for SS are lacking [ 4 ].…”
Section: Current Diagnostic Challenges Encountered By Cliniciansmentioning
confidence: 99%
See 2 more Smart Citations